2022
DOI: 10.1186/s12905-022-01840-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on mental and physical wellbeing in women with fibromyalgia: a longitudinal mixed-methods study

Abstract: Objective The COVID-19 pandemic has strongly influenced psychological and physical health worldwide. The aim of this study was to examine the impact of the pandemic on women with fibromyalgia. Methods This mixed methods pilot study explored measures of pain severity and interference, as well as pain catastrophizing and level of fibromyalgia impact among women with fibromyalgia before and during the COVID-19 pandemic in the USA. Fibromyalgia patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…These findings are consistent with a prior review, which emphasized the impact of social isolation due to the COVID-19 pandemic on physical and mental health in geriatric chronic musculoskeletal pain patients, with loneliness correlated to worsened debility and pain interference [ 22 •]. Although none of the papers in this review looked explicitly at loneliness, we consistently found the influence of decreased mood on the perception of pain, with higher pain catastrophizing [ 8 , 37 , 44 ], pandemic-related fear and stress [ 33 , 35 , 43 ], and anxiety and depression [ 47 , 50 ], all associated with increased levels of pain. With a broader review of published literature and significantly more patient-reported outcomes, our review further emphasizes the role psychological health played in the wellbeing of chronic musculoskeletal pain patients during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent with a prior review, which emphasized the impact of social isolation due to the COVID-19 pandemic on physical and mental health in geriatric chronic musculoskeletal pain patients, with loneliness correlated to worsened debility and pain interference [ 22 •]. Although none of the papers in this review looked explicitly at loneliness, we consistently found the influence of decreased mood on the perception of pain, with higher pain catastrophizing [ 8 , 37 , 44 ], pandemic-related fear and stress [ 33 , 35 , 43 ], and anxiety and depression [ 47 , 50 ], all associated with increased levels of pain. With a broader review of published literature and significantly more patient-reported outcomes, our review further emphasizes the role psychological health played in the wellbeing of chronic musculoskeletal pain patients during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…The sample size ranged from 38 to 965; 86–100% of patients were female. The rate of COVID-19 positive tests was 5–7% in two studies [ 33 , 37 ]. Two other studies excluded patients with a history of COVID-19 infection [ 35 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is needed around this for people with FM. With regards to sleep, a recent Cochrane review suggests a JSQ MCID value of 20% [74] – a value which 100% of the study population achieved, with some improvements as high as 90%. Localised PBMT meta-analyses have not explicitly reported on sleep [134].…”
Section: Discussionmentioning
confidence: 99%